Different Approaches in Radiation Therapy of Craniopharyngioma - Kortmann, Rolf-Dieter (Frontiers in Endocrinology, 2011)
Radiation therapy is a cornerstone in the therapeutic management of craniopharyngioma. The close proximity to neighboring eloquent structures pose a particular challenge to radiation therapy. Modern treatment technologies including fractionated 3-D conformal radiotherapy, intensity modulated radiation therapy, and recently proton therapy are able to precisely cover the target while preserving surrounding tissue, Tumor controls between 80 and in access of 90% can be achieved. Alternative treatments consisting of radiosurgery, intracavitary application of isotopes, and brachytherapy also offer an acceptable tumor control and might be given in selected cases. More research is needed to establish the role of each treatment modality.